2005
DOI: 10.1007/s00125-005-1847-7
|View full text |Cite
|
Sign up to set email alerts
|

Neutral endopeptidase 24.11 and dipeptidyl peptidase IV are both mediators of the degradation of glucagon-like peptide 1 in the anaesthetised pig

Abstract: Aims/hypothesis: The incretin hormone glucagon-like peptide 1 (GLP-1) has antihyperglycaemic effects, but its therapeutic usefulness is limited by its metabolic instability. Dipeptidyl peptidase IV (DPP-IV) is established as the primary inactivating enzyme, but the roles of other enzymes remain unclear. Methods: The effect of candoxatril, a selective inhibitor of neutral endopeptidase (NEP) 24.11, on GLP-1 pharmacokinetics/pharmacodynamics with or without DPP-IV inhibition was examined in anaesthetised pigs. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
131
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(136 citation statements)
references
References 45 publications
4
131
1
Order By: Relevance
“…In vitro studies have demonstrated that neutral endopeptidase 24.11 (NEP) can cleave GLP-1 at multiple sites in both the central and more C-terminal parts of the peptide [8], suggesting a potential role for NEP in the in vivo metabolism of GLP-1. In support of this, a study from this laboratory recently found that NEP inhibition increases the metabolic stability of exogenously administered GLP-1 in anaesthetised pigs [9]. In addition to the substantial enzymatic degradation, several studies have pointed to the kidney as an important mediator in the final elimination of GLP-1 and its metabolites.…”
Section: Introductionmentioning
confidence: 88%
“…In vitro studies have demonstrated that neutral endopeptidase 24.11 (NEP) can cleave GLP-1 at multiple sites in both the central and more C-terminal parts of the peptide [8], suggesting a potential role for NEP in the in vivo metabolism of GLP-1. In support of this, a study from this laboratory recently found that NEP inhibition increases the metabolic stability of exogenously administered GLP-1 in anaesthetised pigs [9]. In addition to the substantial enzymatic degradation, several studies have pointed to the kidney as an important mediator in the final elimination of GLP-1 and its metabolites.…”
Section: Introductionmentioning
confidence: 88%
“…20,21,51 As a result, current GLP-1-receptor agonist therapies require repeated injections to maintain therapeutic plasma concentrations. As an alternative means of raising plasma GLP-1 levels, DPP-IV inhibitors have recently been developed and are now in clinical use for treatment of type-2 diabetes.…”
Section: Aav-mediated Expression Of Glp-1 In Beta-cells Mj Riedel Et Almentioning
confidence: 99%
“…However, its short circulating half-life means that high doses must be administered frequently, which limits its clinical application. The short half-live of GLP-1 is due to its rapid inactivation and clearance under physiological conditions by proteolytic enzymes such as dipeptidyl peptidase-IV (DPP-IV) [4] and neutral endopeptidase (NEP) 24.11 [5].…”
Section: Introductionmentioning
confidence: 99%